Analisis Perilaku FOMO pada Pembelian Boneka Labubu di Indonesia - Yuni Apriliani; Novia Rahmawati; Syamsul Hidayat (Jurnal Manajemen Bisnis Era Digital, 2025)
The Fear of Missing Out (FOMO) phenomenon is one of the psychological factors that influences consumer behavior, especially in the context of purchasing collectible goods. This research aims to analyze FOMO behavior among consumers in Indonesia when purchasing Labubu dolls, a collectible product that is popular among toy lovers. The research method uses a qualitative approach with in-depth interviews with 15 respondents who actively collect Labubu dolls, as well as observations in the fan community. The research results show that FOMO is triggered by limited stock, limited editions, the influence of social media, and pressure from the collector community. Consumers often feel compelled to buy immediately for fear of missing out on the opportunity to own an exclusive product. In addition, social factors, such as competition between collectors and the desire to demonstrate status, also strengthen FOMO behavior. The implications of this research provide insight to producers regarding exclusivity-based marketing strategies and consumer behavior management. This study also contributes to the consumer behavior literature by highlighting the role of FOMO in the context of purchasing collection products in Indonesia.